2022
DOI: 10.3389/fnins.2022.1027116
|View full text |Cite
|
Sign up to set email alerts
|

Neurons and glial cells acquire a senescent signature after repeated mild traumatic brain injury in a sex-dependent manner

Abstract: Mild traumatic brain injury (mTBI) is an important public health issue, as it can lead to long-term neurological symptoms and risk of neurodegenerative disease. The pathophysiological mechanisms driving this remain unclear, and currently there are no effective therapies for mTBI. In this study on repeated mTBI (rmTBI), we have induced three mild closed-skull injuries or sham procedures, separated by 24 h, in C57BL/6 mice. We show that rmTBI mice have prolonged righting reflexes and astrogliosis, with neurologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 96 publications
1
25
0
Order By: Relevance
“…Thus, the effectiveness of treatment may change with more advanced age, which would presumably have a higher burden of established diseases, increased numbers of senescent cells, and age‐related epigenetic modifications. Finally, sex may determine the effectiveness of treatments that influence aging phenotypes (Casaletto et al, 2020 ; Strong et al, 2020 ) and little is known about the effect of senolytic treatment in females and results are mixed (Muralidharan et al, 2022 ; Novais et al, 2021 ; Schwab et al, 2022 ). Thus, future studies should examine effects of senolytic treatment on cognition and brain transcription in females.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the effectiveness of treatment may change with more advanced age, which would presumably have a higher burden of established diseases, increased numbers of senescent cells, and age‐related epigenetic modifications. Finally, sex may determine the effectiveness of treatments that influence aging phenotypes (Casaletto et al, 2020 ; Strong et al, 2020 ) and little is known about the effect of senolytic treatment in females and results are mixed (Muralidharan et al, 2022 ; Novais et al, 2021 ; Schwab et al, 2022 ). Thus, future studies should examine effects of senolytic treatment on cognition and brain transcription in females.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, DNA damage driven gene fusions were detected in excitatory cortical neurons from AD patients and suggested to contribute to differential gene expression in neurons in the disease, including alterations to senescence pathways 36 . Similarly, glial and cortical neuron senescence has been reported following traumatic brain injury, where neurons accumulate DNA double strand breaks, loss of nuclear lamina integrity, and gene expression changes related to senescence processes [37][38][39] . Given the growing body of data that neuronal senescence occurs during aging and in response to various forms of injury and stress, it begs the question whether these characteristics of senescence arising in neurons is simply an outcome of accumulated injury over time, overwhelming the neuron's intrinsic repair capacity, and impeding its homeostatic functions.…”
Section: Discussionmentioning
confidence: 83%
“…For instance, DSBR via NHEJ declines with age in women, but not in men in peripheral blood lymphocytes [ 45 ]; female cells undergo senescence, while male cells undergo apoptosis following UV irradiation in rat vascular smooth muscle cells [ 46 ]. Consistent with these findings, a recent study showed that the neurons and glial cells of mice that underwent repeated mild traumatic brain injury acquired a senescent signature, with female mice having higher levels of DNA damage, lower levels of the senescence protein p16, and lower levels of the cyclic GMP–AMP synthase stimulator of interferon gene (cGAS-STING) signaling proteins compared with their male counterparts [ 47 ]. Sex differences in cellular senescence may underlie sex-specific disease outcomes [ 48 ].…”
Section: Introduction Of Cellular Senescence and The Saspmentioning
confidence: 70%